The adverse event profile of brivaracetam: A meta-analysis of randomized controlled trials. (February 2017) - Zhu, Li-na; Chen, Deng; Chen, Tao; Xu, Da; Chen, Si-han; Liu, Ling
Highlights: Serious AEs, overall withdrawal, AE-related withdrawal and psychiatric adverse events (PAEs) were not significantly associated with BRV treatment. BRV was also not significantly associated with a heightened risk of AE-related withdrawal and PAEs with increasing doses. Three AEs (dizziness, fatigue, and back pain) were found to be significantly associated with BRV treatment. Abstract: Purpose: To comprehensively evaluate the adverse events (AEs) significantly associated with brivaracetam (BRV) treatment in a large selection of randomized control trials. Methods: We conducted an online database search using Pubmed, Embase, Cochrane Online Library, and Clinicaltrial.gov for all available randomized control trials (RCTs) that investigated the therapeutic effects of brivaracetam. Serious AEs (SAEs), withdrawal, and treatment-emergent adverse effects were then assessed for their association with brivaracetam. Finally, a meta-analysis was performed using Review Manager 5.3 software. Results: Eight RCTs with a total of 2505 patients were included in our study, 1178 of which were randomized with respect to brivaracetam (BRV). Serious AEs, overall withdrawal, AE-related withdrawal and psychiatric adverse events (PAEs) were not significantly associated with BRV treatment. BRV was also not significantly associated with a heightened risk of AE-related withdrawal and PAEs with increasing doses. Of the 17 AEs included in our meta-analysis, three AEs (dizziness, fatigue, and back pain) were found to be significantly associated with BRV treatment. But we did not find that the risk of them was obviously increasing with the increasing doses. Conclusion: This meta-analysis showed that BRV treatment was reasonably tolerated by patients and rarely caused serious AEs. Further clinical studies will be needed to more concretely determine the safety and tolerability profile of BRV.